Correction: Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2026)

Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2025)
The climate of the Maritime Continent, including Singapore, is influenced by a wide range of tropical drivers including the El-Niño Southern Oscillation (ENSO), the Indian Ocean Dipole (IOD), the Madden–Julian Oscillation (MJO), and equatorial wave activity. In Singapore, the rainfall pattern is often marked by episodes of short intense rainfall bursts, primarily driven by mesoscale convective systems, such as Sumatra squall lines. These episodes often result in local flash floods and strong wind bursts. Here we analyse 33 years of Sumatra squalls affecting Singapore and investigate the potential impact of the main modes of climate variability and atmospheric equatorial tropical waves. Highlighted results are that, on average, Sumatra squalls originate from Sumatra and the Strait of Malacca, make landfall over Singapore primarily in the morning and last about 2 h, and are more frequent from April to November. These squalls tend to be more frequent under La Niña conditions, which are associated with locally warm sea surface temperature anomalies and favourable atmospheric anomalies over the Maritime Continent region. On intraseasonal scale, the MJO may play a role in setting the westerlies and enhancing convective conditions favorable for the squalls to intensify and propagate eastward. Convectively-coupled Kelvin waves are important for the initiation and eastward propagation of the squalls over Sumatra and the Strait of Malacca, while equatorial Rossby, and mixed Rossby gravity waves influence their meridional propagation toward Singapore.